The impact of mitomycin C in endoscopic sinus surgeries: a comprehensive review - Manglik, Shivangi; Kalra, Vijay (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2024)
Chronic rhinosinusitis (CRS) is an inflammation of the nasal and paranasal sinus linings, often resulting in various debilitating symptoms. Functional endoscopic sinus surgery (FESS) is a common treatment for CRS, aiming to alleviate symptoms by restoring sinus drainage and mucosal repair. However, postoperative complications, including adhesion formation, remain a concern. This systematic review aims to evaluate the effectiveness of mitomycin-C (MMC) in reducing postoperative complications, particularly adhesion formation, in patients undergoing ESS. A systematic review of available evidence on the role of MMC in FESS was conducted. Studies were selected based on predefined inclusion criteria, and relevant data were extracted and synthesized. Nineteen studies met the inclusion criteria, encompassing a total of 763 subjects. The majority of studies reported a reduction in postoperative adhesion formation with MMC use, although statistical significance varied. MMC dosages and application methods varied across studies, contributing to heterogeneity in outcomes. Overall, MMC showed promise in reducing adhesion formation and improving surgical outcomes in FESS. However, further high-quality, prospective, randomized controlled trials are warranted to establish optimal dosage, application methods, and long-term efficacy of MMC in FESS for CRS.